1988
DOI: 10.1254/jjp.48.499
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Methotrexate on Local Cerebral Blood Flow in Conscious Rats

Abstract: Abstract-The effect of methotrexate (MTX) on local cerebral blood flow (I-CBF) was studied with autoradiographic[14C]-iodoantipyrine methods in normal con scious rats. I-CBF was reduced by 30-57% in the rats given MTX (100 mg or 200 mg/body) as compared to that in the saline injected control group, but no dose dependent effect was observed. The mechanism of I-CBF reduction by MTX was discussed.The administration of high-dose metho trexate (MTX) is now widely used in the treatment of osteogenic sarcoma and chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
1

Year Published

1999
1999
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 5 publications
0
8
0
1
Order By: Relevance
“…MTX was infused into the femoral vein of conscious male SpragueDawley rats for 2 h and cerebral blood flow was measured with [ 14 C]iodoantipyrine. Compared to control conditions, MTX reduced cerebral blood flow in a number of regions, including the hippocampus and frontal cortex [23]. Our PET results show a transient decrease in FDG uptake in the hippocampal region.…”
Section: Discussionmentioning
confidence: 49%
“…MTX was infused into the femoral vein of conscious male SpragueDawley rats for 2 h and cerebral blood flow was measured with [ 14 C]iodoantipyrine. Compared to control conditions, MTX reduced cerebral blood flow in a number of regions, including the hippocampus and frontal cortex [23]. Our PET results show a transient decrease in FDG uptake in the hippocampal region.…”
Section: Discussionmentioning
confidence: 49%
“…Earlier results of human brain perfusion in SPECT showed defects in the cortical areas and the basal ganglia (15,20,21). Also, a brain perfusion study in rats with PET indicated that CBF reduced in all brain regions after MTX infusion (16). In this work, selected ROIs (the cortex, the sub-cortex, the thalamus, or deep structures) were taken into account as preferable areas of the MTX exposure-induced changes in rCBF or white matter.…”
Section: Discussionmentioning
confidence: 95%
“…CMR glu is found to reduce 20%-40% due to MTX exposure (12)(13)(14). Exposure to MTX may cause either local (cortical, sub-cortical, periventricular) or diffuse white matter changes (hypo/hyperintensity) in the anatomic MRI or computed tomography (17)(18)(19)(20); however, functional changes in brain perfusion have only been studied in SPECT and PET (15,16,20,21).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MTX reduces the requirement for systemic steroids and stabilizes or decreases the level of intraocular inflammation. In addition to its effect as immunomodulatory drug in rheumatoid disease, studies in other fields have reported, for example, vascular occlusion after intraarterial therapy with MTX [33] and reduction of local cerebral blood flow by MTX [30], suggesting a potential use of MTX as antiangiogenic agent.…”
Section: Introductionmentioning
confidence: 99%